2019
DOI: 10.3389/fmats.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

To Improve Total Knee Prostheses Performance Using Three-Phase Ceramic-Based Functionally Graded Biomaterials

Abstract: One of the common issues that occur after total knee replacement surgery is the aseptic loosening. The problem usually occurs after about 15 years from the surgery. The destructive effects of residual particles due to wear, the stress shielding effect, and micro-movements are the causative factors for this type of loosening. In this research, using the advantages of functionally graded biomaterials (FGBM), it is tried to design a prosthetic system that can reduce the above-mentioned effects. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This is a better approach than dividing the tibial implant into different layers/ slices and then assigning different properties to each layer as done by the earlier researchers. [28][29][30]34 In the layered approach, the material variation is not gradual between the interfaces of the subsequent layers. Additionally, in this approach, the number of elements can be increased to achieve a more continuous and uniform FGM distribution.…”
Section: Fgm Properties Of the Tibial Implantmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a better approach than dividing the tibial implant into different layers/ slices and then assigning different properties to each layer as done by the earlier researchers. [28][29][30]34 In the layered approach, the material variation is not gradual between the interfaces of the subsequent layers. Additionally, in this approach, the number of elements can be increased to achieve a more continuous and uniform FGM distribution.…”
Section: Fgm Properties Of the Tibial Implantmentioning
confidence: 99%
“…27 FGMs have already been successfully used in total hip replacement (THR) 26,[28][29][30][31] and total knee replacement (TKR). [32][33][34][35] Enab et al 26 proposed FGM hip implants of different titanium alloys layered with HA and reported an increase in bone von Mises stress with FGMs. Moussa and Yadav 28 performed a study on FGM stem for the femoral component of THR, and showed lesser stress shielding with FGM implants compared with Ti alloy implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the gradation direction considerably affects the bone adaptation procedure. The results showed that using a radial FGM with low-stiffness material in the outer layer and less metal composition significantly improves the bone remodelling behaviour., Ayatollahi et al, [55] improve the performance of the bone prosthesis system and prevent the aseptic loosening in a total knee replacement surgery using two types of ceramic based functionally graded biomaterials, alumina based and zirconia based FG biomaterials. Both the alumina based and zirconia based FG biomaterials showed significantly better performance compared to commonly used Cr.Co prosthesis.…”
Section: Biomedical Cooilacilppamentioning
confidence: 99%
“…Many different studies have created FGBMs by varying the size of the lattice unit cell throughout the material to alter the stiffness of the scaffold in different locations (Mahbod and Asgari, 2019;Torres et al, 2016;Zhang et al, 2019). Ayatollahi et al (2019) have proposed a 3-phase ceramic based FGBM, which uses HA, alumina or zircona, and titanium all within the same component to provide different material properties in different locations on a knee implant. The use of FGBMs is also being investigated to develop artificial blood vessels.…”
Section: Improving the Mechanical Properties Of Implants Using Ammentioning
confidence: 99%